THE ART AND SCIENCE OF PROJECT MANAGEMENT: STRATEGIES FOR SUCCESS - Asliddin, Daminov (Journal of Higher Education and Academic Advancement, 2025)
Objective:  Project management is essential across industries for achieving strategic objectives efficiently and effectively. Modern organizations operate in dynamic environments that demand timely delivery, budget adherence, and high-quality outcomes, relying on structured project management frameworks to ensure success. However, there is limited integrative analysis of how various methodologies, including Agile, Waterfall, and Lean, address practical challenges such as scope creep, resource allocation, and stakeholder engagement to optimize project outcomes. This article aims to explore the fundamental principles, methodologies, and tools of project management, highlighting their roles in enhancing efficiency, minimizing risks, and delivering stakeholder value. Method: The study elucidates that Agile methodology offers flexibility and iterative feedback integration, the Waterfall model provides linear clarity for well-defined projects, and Lean focuses on eliminating waste and optimizing processes. Result: Effective project management involves navigating the project lifecycle phases—initiation, planning, execution, monitoring, and closure—while proactively addressing challenges to ensure project alignment with organizational goals. Novelty: This work synthesizes diverse methodologies with practical insights on technological advancements, such as cloud-based collaboration and data analytics, demonstrating their transformative impact on traditional project management practices. The findings imply that adopting appropriate methodologies, embracing innovation, and fostering value-driven mindsets enable project managers to navigate complex landscapes, enhance team adaptability, and contribute to sustainable organizational growth.